Analisis Permintaan Air Perusahaan Daerah Air Minum (Studi Empiris Pada PDAM Tirta Satria di Kota Purwokerto) - Retnowati, Diah; Susanti, Eli; Astuti, Ratna Puji; Purnomo, Sodik Dwi; Lestari, Herwiek Diyah; Harsuti, Harsuti (PPJP Universitas Lambung Mangkurat, 2023)
This study aims to analyze the effect of family income, number of family members, water use costs, length of time as a customer, yard area, other water sources, and installation costs on PDAM water demand in Purwokerto City. The research locations were four sub-districts in Purwokerto, including East Purwokerto, West Purwokerto, North Purwokerto, and South Purwokerto Districts. The research method used is multiple linear regression. The results showed that family income, number of family members, cost of water use, and yard area significantly positively affected PDAM water demand in Purwokerto City. Meanwhile, other water sources significantly negatively affect PDAM water demand. The length of time as a customer and installation costs do not affect PDAM water demand in Purwokerto City.